If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 450 + 12t = 522 Solving 450 + 12t = 522 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-450' to each side of the equation. 450 + -450 + 12t = 522 + -450 Combine like terms: 450 + -450 = 0 0 + 12t = 522 + -450 12t = 522 + -450 Combine like terms: 522 + -450 = 72 12t = 72 Divide each side by '12'. t = 6 Simplifying t = 6
| 6y-9=-3y+9 | | 3+y=1 | | 6x-25=18 | | 7x+17=88 | | -11y-2=-123 | | 5x+12=81 | | -10y+9=119 | | 3x+12=, | | -2y=-14 | | 600+14t=670 | | 25=3x+4 | | 7x+19=19x-8 | | logx+4=8 | | 16c^2-25=0 | | 7+2(x-5)=13 | | 6y-9=-3x+9 | | 550+16t=598 | | 2x(x-5)(2x+1)=0 | | 2x-15=43 | | 2x+59=4012 | | x^3+2x^2-16x=32 | | y+12=-35 | | -1.7y=-13.6 | | -16t^2+48t+160=160 | | 2-y+2y=7 | | -1.7=-13.6 | | 15=9y-4y | | 4x=193 | | 9x-4x=19 | | -25=10y | | R-9.3=4.2 | | 5=1/2(2x-4)-2x |